DEVELOPMENT OF A METHOD FOR PRODUCING SOLAR CELLS BASED ON IODINE PEROVSKITE WITH n-i-p-STRUCTURE ON SnO2 - Azimov J.T. (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
The article tested methods for producing solar cells based on iodide perovskite with an n-i-p structure on SnO2 and measured the current-voltage characteristic (CVC) of these cells. The theoretical and experimental studies carried out are important for the creation of efficient 3rd generation solar energy converters based on perovskites.